"Science fiction without gadgets" and the normalization of cognitive impairment: Reassessing Charly (1968). (1st June 2022) - Miller, Gavin
Abstract : The motion picture Charly (1968) stars Cliff Robertson as a cognitively impaired bakery worker who undergoes an experimental intelligence-enhancing neurosurgical procedure that temporarily grants him superhuman intelligence. Although Charly may seem merely to endorse the dominant sf trope of cure for disability, it offers a complex and equivocal engagement with the growing "normalization" agenda in the 1960s US, by which cognitively impaired persons were moved out of institutions in order to lead lives as close to culturally normative as possible. The movie partly affirms normalization and its social critique through the narrative continuity between Charly before and after his neurosurgery, and by the inclusion of cognitively impaired children within the cast. Robertson's performance also conveys Charly's deliberate performance as an object of ridicule within his workplace. However, Charly also gestures to ongoing anxieties about the sexuality of cognitively impaired persons, and it questions the normative valorization of intelligence in modern society. Although the movie's plural visual style was criticized by contemporary reviews, its aesthetic offers a dialogic model of the self, and resists the centripetal tendency to filmmaking within a single authoritative or neutral style.